REPRODUCTIVE HEALTH COUNSELING AND MATURING OF MARRIAGE AGE AS AN EFFORT TO INCREASE ADOLESCENTS' AWARENESS AND KNOWLEDGE ABOUT ADOLESCENT HEALTH - Dia Gutami, Anggie; Anugrah Febrianti, Nanda; Angraini, Dista (Mulawarman International Conference on Tropical Public Health, 2025)
Background : The main problem in adolescent reproductive health (ARH) in Indonesia is the lack of knowledge about reproductive health and low awareness of the importance of Marriage Age Maturation (MAM). This also happens in Tengin Baru Village, Sepaku District, where many teenagers do not understand the importance of maintaining reproductive health and the negative impacts of early marriage Objective : Therefore, the aim of this service is to increase teenagers' knowledge about reproductive health and PUP through outreach programs. Research Methods/ Implementation Methods : The method used in this service was counseling which involved 26 teenagers from Hamlet 1 of Tengin Baru Village as the main participants, with an additional 17 guests also attending. The activity begins with completing a pre-test to measure participants' initial knowledge, followed by providing material through presentations and interactive discussions. The program also includes educational video screenings to improve participants' understanding. Results : Evaluation is carried out by completing a post-test to see the increase in participant knowledge. The results show an increase in knowledge of 13.6% after counseling, which can be seen from the results of the post-test compared to the pre-test. This shows that the outreach program has succeeded in increasing teenagers' understanding of reproductive health and MAM. Conclusion/Lesson Learned : . In conclusion, this counseling went well and succeeded in increasing teenagers' knowledge about reproductive health and PUP. It is recommended that future counseling methods be more attractive to maintain participant enthusiasm, as well as choosing a more appropriate implementation.